ANALISIS KUNJUNGAN RUMAH DALAM PENANGANAN KASUS ORANG DENGAN GANGGUAN JIWA PASCA PENDATAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (Studi kasus di Puskesmas Padangsari Kota Semarang) - Nur Laili Agustin; Ayun Sriatmi; Rani Tyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The number of ODGJ cases in Padangsari Public Health Center in Semarang has increased from 2016 to 2018. The increase in the number of patients must be balanced with an increase in the process of providing Puskesmas services specifically for mental disorders. The purpose of the study was to analyse home visit process in handling ODGJ cases after the collection of PIS-PK data at Padangsari Health Center, Semarang City. This research is a qualitative research with a descriptive analytic approach. Data collection was carried out by an in-depth interview. The research subjects were the current ODGJ Program Holders, Health Cadres in the work area, and PIS-PK Coordinator Padangsari Health Center as the main informant.. Whereas triangulation informants were the person in charge of the Health Office’s PIS-PK, Head of Padangsari Community Health Center, ODGJ Family and Referral Hospital Health Workers. Factors analyzed include input, process, and environmental variables in home visit handling ODGJ cases. The results of this study are that in the home visit process of handling ODGJ cases after PIS-PK data collection there is shows that in the home visit process in handling ODGJ cases, only a few houses have been visited. Of the 64 cases, there are still many ODGJ families who have not been conducted regularly. In this process, ODGJ families tend not to be visited because they are closed or ashamed. Health workers ask for help from the head of the local RT to be communicated to the families of the ODGJ concerned. There are several obstacles in the home visit process of handling ODGJ cases after the collection of PIS-PK data at Padangsari Public Health Center in Semarang City which have an impact on the running of home visit process that is less than optimal.